Optical fibre CO2 sensing for monitoring the effects of tissue loading - Afroze, Nadia (2023)
The ultimate objective of this PhD thesis is to develop and characterise optical fibre sensors for carbon dioxide (CO2) monitoring during tissue loading. CO2 is a reliable marker for the early detection of pressure ulcers (PUs). In this thesis, a reflection mode optical fibre CO2 sensor (OFCS) was developed for early prediction of PUs formation. Transcutaneous CO2 probes based on electrochemical sensing are commercially available for measurement of arterial partial pressure. It is therefore important to consider the advantages of OFCS in terms of device form and performance. The most important potential advantage is that an OFCS is very thin (core diameter, Ø 62.5 µm, cladding diameter, Ø 125 µm) and flexible and so could be used for continuous monitoring during patient treatment or during everyday life. Furthermore, electrochemical sensors require skin heating, temperature calibration and use of contact gel; OFCS can potentially monitor without. Therefore, if comparable performance to electrochemical sensing could be achieved, then there is an opportunity for OFCS to be widely adopted for monitoring tissue breakdown.